A review of the relation between dissociation, memory, executive functioning and social cognition in military members and civilians with neuropsychiatric conditions. (September 2016) - McKinnon, Margaret C.; Boyd, Jenna E.; Frewen, Paul A.; Lanius, Ulrich F.; Jetly, Rakesh; Richardson, J. Donald; Lanius, Ruth A.
Abstract: Dissociative experiences, involving altered states of consciousness, have long been understood as a consequence or response to traumatic experiences, where a reduced level of consciousness may aid in survival during and after a traumatic event. Indeed, the dissociative subtype of post-traumatic stress disorder (PTSD-DS) was added recently to the Diagnostic and Statistical Manual of Mental Disorders, 5th edition (DSM-5). Dissociative symptoms are present across a host of neuropsychiatric conditions, including PTSD, psychotic spectrum illnesses, anxiety and mood disorders. Transdiagnostically, the presence of dissociative symptoms is associated with a greater illness burden and reduced treatment outcomes. Critically, dissociative symptoms are related to impaired performance on measures of attention, executive functioning, memory, and social cognition and may contribute to the widespread cognitive dysfunction observed across psychiatric illnesses. Despite this knowledge, the relation between dissociative symptoms and reduced cognitive function remains poorly understood. Here, we review the evidence linking dissociative symptoms to cognitive dysfunction across neuropsychiatric disorders. In addition, we explore two potential neurobiological mechanisms that may underlie the relation between dissociative symptoms and cognitive dysfunction in trauma-related neuropsychiatric conditions. Specifically, we hypothesize that: 1) functional sensory deafferentation at the level of the thalamus, as observed in the defence cascade model of dissociation, may underlie reduced attention and arousal leading to progressive cognitive dysfunction and; 2) altered functional connectivity between key brain networks implicated in cognitive functioning may represent a critical neurobiological mechanism linking dissociative symptoms and cognitive dysfunction in patients with PTSD-DS and transdiagnostically. Highlights: The relation between dissociation and cognitive dysfunction is reviewed. Functional sensory deafferentation at the level of the thalamus may lead to progressive cognitive dysfunction. Altered functional connectivity between key intrinsic neural networks may underlie cognitive dysfunction. Clinical and treatment implications are discussed.